Geriatric and Student Perceptions following Student-led Educational Sessions - Kristin Janzen; Lauren N. Kormelink; Lindsay Saum; Sarah A. Nisly (University of Minnesota Libraries Publishing, 2018)
Objective: The objective of this study was to measure the effect of student-led educational events on geriatric patient and student participant perceptions in a community setting. Methods: Students led three events at a senior community center, focusing on learning and memory, sleep hygiene, and arthritis pain. The participants were geriatric patients who themselves were providers of support to homebound peers ("clients") through an independently organized program. Geriatric participants completed pre- and post-event surveys to measure changes in familiarity with the topics. Student participants also completed pre- and post-event surveys that tracked changes in their comfort in working with the geriatric population. Results: Each event demonstrated at least one positive finding for geriatric patients and/or their clients. Students reported increased comfort in working with and teaching the geriatric population following the first and third events, but not the second. Conclusion: Student-led educational sessions can improve perceived health-related knowledge of geriatric participants while simultaneously exposing students to the geriatric patient population. Overall, both students and geriatric participants benefited from these events. Practice Implications: Incorporation of single, student-led educational events could be mutually beneficial to students and the elderly population in the community and easily incorporated into any healthcare curriculum. Funding:This work was supported by a Butler University Innovation Fund Grant. Treatment of Human Subjects: IRB review/approval required and obtained   Type: Original Research